Land Cover and Climate Change Impact on River Discharge: Case Study of Upper Citarum River Basin - Kuntoro, Arno Adi; Cahyono, Muhammad; Soentoro, Edy Anto (Journal of Engineering and Technological Sciences, 2018)
The Upper Citarum River Basin is the main catchment area of the Saguling Dam, the most upstream of three cascade dams in the Citarum River Basin. During the last 30 years, rapid economic development has led to an increase of water extraction and land conversion from green area to developed area. Also, evidence of climate change can clearly be seen from the climatological records of a number of climatology stations in this basin over the last few decades. In this study, the effect of anthropogenic and climate change in the Upper Citarum River Basin river discharge was simulated using the Sacramento Catchment Model. Historical river discharge, rainfall, climatology, and land cover from 1995 to 2009 were used for model calibration and verification. The multi-model mean monthly rainfall and the temperature projection taken from Coupled Model Intercomparison Project 5 (CMIP5) for the RCP6 and RCP8.5 climate change scenarios were statistically downscaled and used as input for a simulation of future river discharge from 2030 to 2050. The result showed that the combination of anthropogenic and climate change may result in a significant decrease of low flow in the Upper Citarum River Basin. This study underlines the importance of land cover and climate change factors for future infrastructure planning and management in the Upper Citarum River Basin.